Consideraciones contractuales del outsourcing, para el desarrollo de Software (Outsourcing contractual considerations, for Software development) - Cantú Mata, José Luis; Palomo González, Miguel Ángel; Torres Castillo, Fernando (Facultad de Contaduría Pública y Administración U.A.N.L., 2011)
Abstract. Software Outsourcing has become a solution for organizations due to different reasons that companies consider to get some benefit from doing any business process. After evaluating what those benefits and the decision to resort to outsourcing, the company considers an outsourcing contract and becomes a client company. The contents of the outsourcing contract is based on factors that companies consider to hire an outsourcing provider for software development. Based on the significant investment in recruiting software provider for businesses in Mexico, performed a literature review to identify key variables that, in principle, influence the hiring of a vendor whose business is software development. Resumen. El Outsourcing de Software se ha convertido en una solución para las organizaciones, debido a diferentes motivos que las empresas consideran para obtener ciertos beneficios al realizar algún proceso de su negocio. Después de evaluar cuales son esos beneficios y se toma la decisión de recurrir al Outsourcing, la empresa considera un contrato de Outsourcing y pasa a ser una empresa cliente. El contenido del contrato de Outsourcing, está basado en factores que las empresas consideran para contratar a un proveedor de Outsourcing para el desarrollo de Software. Partiendo de la importante inversión en la contratación de proveedores de Software por las empresas en México, se realiza una revisión de literatura para identificar las principales variables que, en principio, influyen en la contratación de un proveedor, cuya actividad es el desarrollo de software.